Cross-property deep transfer learning framework for enhanced predictive analytics on small materials data - Vishu Gupta (Nature Portfolio, 2021)
Artificial intelligence and machine learning can greatly enhance materials property prediction and discovery. Here the authors propose cross-property transfer learning to build accurate models for dozens of properties with limited data availability.